Challenging Institutional Racism in International Relations and Our Profession: Reflections, Experiences, and Strategies. (September 2021) - Delatolla, Andrew; Rahman, Momin; Anand, Dibyesh; Caesar, Mary; Haastrup, Toni; Adiong, Nassef Manabilang; Parashar, Swati; Youde, Jeremy
Attempts to create a more inclusive discipline and profession have been commended by many and derided by some. While these attempts have pushed for change, particularly with regards to more equal representation of gender and race among faculty, policies aimed at creating a more inclusive environment are often tokenistic, administrative and bureaucratic, and fail to address structural and institutional practices and norms. Moreover, the administrative and bureaucratic policies put into place are generally targeted at a single categorical group, failing to take into account the manner in which identities are intersecting and overlapping. Equality, Diversity and Inclusion often gets driven by Human Resources and Marketing rather than owned by the wider university. This forum draws from a variety of contributions that focus on describing the lived realities of institutional racism, its intersections with other forms of discrimination, and strategies for change. In putting together this forum, we do not aim to create a checklist of practical steps. Instead, we hope to signpost and make visible the successes and failures of previous challenges and future possibilities that must be taken by both faculty and administrations.